The Effect of Green Fertilizer Application Apu-Apu (Pistia Stratiotes) and Plant Growth Regulators on the Growth and Production of Lettuce (Lactuca Sativa L.) - Simanjuntak, Pantas; Panataria, Lince Romauli (ITScience (Information Technology and Science), 2024)
This study aims to determine the effect of green fertilizer apu-apu and plant growth regulators on the growth and production of lettuce (Lactuca sativa L.). This study used a randomized block design (RAK) with two factors. The first factor is green fertilizer Apu-Apu with the symbol (K) consisting of 3 levels: K1 = 1 kg/plot, K2 = 1.5 kg/plot and K3 = 2 kg/plot. The second factor is plant growth regulators with the symbol (P) consisting of 4 levels: P0 = control (no treatment), P1 = 2 cc / l water, P2 = 4 cc / l water and P3 = 6 cc / l water. The results showed that green fertilizer apu-apu up to a dose of 2 kg/plot significantly increased the Height of fresh weight per plant, wet weight per plot and root weight per plot but did not affect plant height. The provision of plant growth regulators significantly increased plant height, wet weight per plant, wet weight per plot and root weight per plot. The administration of growth regulators up to a concentration of 6 cc/l of water resulted in the highest wet weight per plant and wet weight per plot. The interaction between apu-apu green manure and growth regulators did not significantly affect plant height, number of leaves, wet weight per plant, wet weight per plot and root weight per plot.